The impact of bilateral investment treaties on FDI inflows into India: Some empirical results - Jaivir Singh; Vatsala Shreeti; Parnil Urdhwareshe (Indian Council for Research on International Economic Relations (ICRIER), 2020)
Commencing in the 1990s, India signed a number of bilateral investment treaties (BITs), however, after a spate of adverse investor-state dispute settlements (ISDS), India has recently denounced all its erstwhile investment treaties. New investment treaties now need to be negotiated on the basis of a new Model Treaty that substantially privileges state rights over investor rights. We study the impact of bilateral investment treaties on foreign direct investment inflows into India over the period these treaties were in force, to give us a sense whether the advent of the new regime will perhaps subtract some incentives in relation to FDI inflows. The impact of such institutional variables on FDI have been typically studied using large cross-country data sets - our work here is distinct in that we try to capture the effects of international investment agreements on foreign direct investment inflows specifically into India. To do this we construct an empirical model drawing on the Gravity Model, and estimate parameters using Generalised Method of Moments. Our results show that while the individual signing of bilateral investment treaties does not influence the inflow of foreign direct investment, the effect of the cumulative bilateral investment treaties signed is statistically very significant. The significance of the cumulative variable suggests that the spillover effect of signing a series of bilateral investment treaties are important, signaling a regime of overall protection to investors. The importance of institutional variables in influencing FDI into India tells us that overall participation in a system governed by international investor agreements did influence the inflow of foreign direct investment positively.
Keywords: F21; F23; F550; F63; K33; O19; C22; C29; 330; BITS; International investment Agreements; FDI inflows; Gravity Model; Generalised Method of Moments